Proceso de atención de enfermería en paciente de 20 años con hemorragia post parto más anemia severa. - Terán Cruz, Tiffani Thalía (2021)
Hemorrhage within the postpartum period is one of the most overwhelming complications in obstetric emergencies and is conceptualized as the loss equal to or greater than 1000 milliliters of blood after a normal physiological delivery or cesarean section that generally occurs within the first 24 hours , there are different etiologies, among the main ones we have, pathologies associated with the muscular tone of the uterus (uterine atony), pathologies associated with tissue retention (placental accreta), pathologies associated with birth canal injuries (birth canal tears. ) pathologies associated with alterations in clotting times, for a correct diagnosis use is made of complementary studies and examinations (blood profile, blood clotting times, etc.) as well as identification of the clinical picture, the treatment is based on the base etiology, which includes the administration of uterine-tonic, replacement of fluids and blood transfusions and in more serious cases the immediate approach of surgical procedures. The following clinical case study was conducted in a 20-year-old female patient with a diagnosis of immediate physiological puerperium plus postpartum hemorrhage plus severe anemia to whom the nursing care process was applied based on the patterns according to the model. by Marjorie Gordon, in addition the taxonomies NANDA, NOC and NIC were used as tools for the creation of diagnoses, and nursing interventions that guaranteed the recovery of the state of health of the patient during.